Castle - Gravett, Christopher, 1951- (New York : Knopf : Distributed by Random House, 1994)
Explores the medieval world of castles looking at their history, how they were built, and what life was like inside them.
Includes index.
"A Dorling Kindersley book"--T.p. verso.
Wilson's Children.
Notable/Best Books (A.L.A.).
School Library Journal.
6.7
Keywords: Fortification -- Europe -- History -- Juvenile literature; Castles -- Europe -- History -- Juvenile literature; Castles; Fortification; Castles; Fortification; Fors and Fortification -- Europe -- History; Castles -- Europe; Castles